Effectiveness of Finishing School Programme in Enhancing Graduates Employability - Aidarohani, Samsudin (2009)
Lack of soft skills among graduates in Malaysia is said as one of the reasons why they are unemployed although they have excellent academic results. To address this problem the Ministry of Higher Education has directed the institution of higher learning in Malaysia to establish a program called Finishing School, purposely to equip graduate with the soft skills to ensure their employability. Hence this study was conducted to identify the effectiveness of this program in enhancing employability of graduates in Malaysia. To assess the effectiveness of this program, a total of 892 graduates from four universities namely USM, UUM, UniMAP and UIAM have been selected as respondent. Effectiveness of this program is measured through the perspective of respondents on the ability of Finishing School programs in improving their soft skills and opportunities to obtain employment. In addition, Multinomial Logit model is also used because the various labour market outcome of graduates. In addition this study also utilizes information from interviews conducted on several private companies to obtain information related to the soft skills that need to be possessed by the graduates to increase their employability. Result from stocktaking shows that institutions of higher learning have offered various soft skills that have been outlined by the ministry of higher education. Therefore, institutions of higher education must find a way on how to make Finishing School program more attractive in order to increase the participation among graduating students.